Playful brains: a possible neurobiological pathway to cognitive health in aging - Golland, Yulia; Ben-David, Boaz M.; Mather, Mara; Keisari, Shoshi (Frontiers in Human Neuroscience, 2025)
Healthy cognitive aging emphasizes preserving cognitive functions essential for independence and well-being. Developing interventions that promote cognition and resilience in older individuals is crucial. Social playfulness, characterized by spontaneity and mutual enjoyment, allows individuals to step away from routine roles and engage in novel and surprising exchanges. Emerging evidence suggests that social playfulness is a promising approach for supporting cognitive functions in aging in a joyful and engaging way. In this theory and hypothesis manuscript, we propose a neurobiological pathway mediating the effects of social playfulness on cognition. Playful interactions generate high levels of uncertainty, requiring continuous adaptation and exploration. We suggest that these demands engage the locus coeruleus-noradrenaline (LC-NA) system, which is crucial for navigating uncertainty and sustaining arousal and flexibility needed to adapt to the dynamic and unpredictable nature of playful interactions. Importantly, the collaborative and safe environment of playfulness transforms this uncertainty-driven noradrenergic activation into an engaging and rewarding experience, enhancing focus, positive affect, and flexibility. In older adults, where LC-NA functionality may decline with age, social playfulness could counteract cognitive decline by upregulating this system. We review evidence linking LC-NA integrity to cognitive health and explore how playfulness might mitigate the deterioration of cognitive functioning by training executive functions and promoting novelty and exploration. This framework bridges neuroscience, cognitive psychology, and creative-arts therapies, highlighting social playfulness as a tool for healthy aging. We emphasize the need for further research to validate this hypothesis and explore its implications for designing interventions that leverage social playfulness to enhance cognitive resilience in older populations.